Perancangan Fasilitas Duduk Publik untuk Meningkatkan Interaksi Sosial Antar Mahasiswa Universitas Kristen Petra Surabaya - Devina, Ayu Nadia (Intra, 2015)
The development of modern human lifestyle at this time gives rise to a variety of impacts. One of its effects is the increasing individuality which causes lack of direct social interaction. In a smaller scale this thing happens among students of Petra Christian University in Surabaya. A public facility that can accommodate and stimulate social interaction activities on campus is needed, the facilities of public seating. Designed with knock down system, this facility is dynamic in accordance with the activities of social interaction among students on campus. It is expected by designing this public seating facilities on campus social interactions can be increased and can add to the dynamics of student activities on campus.